Modernisation énergétique et réorganisation régionale des Andes méridionales : les matérialités inattendues du Gazoduc Sud Péruvien - Nina Montes de Oca; Sébastien Velut (Revue de Géographie Alpine)
Since 2004, gas operations in Camisea have been restructuring the Peruvian energy system. The pivot of Peruvian energy production has shifted from the high mountains and their water resources to the Andean foothills, and a vast political program of gas network construction and gas massification was launched in the mid-2000s. This article aims to question the materiality of the energy change implemented in the southern Andean region of the country, which does not involve renewable energies, but which crystallizes around a gas pipeline project and its outputs (thermal power plants, urban gas networks, etc.). From an interpretive framework articulating the development imaginaries development with a critical approach of the materiality of energy modernization, this article builds its analysis on a variety of sources combining field work and the documents published on the project in order to map energy change in this region, and the values associated. While the symbolic object of the Southern Peruvian Gas pipeline is presented in discourses as the triumphant advent of energy modernization in which the state is the central actor, it has given rise to fragmented energy materialities, and a distorted energy change, moving away from its primary social objective.